2015
DOI: 10.1136/bmj.h3867
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence of gastric cancer among patients with gastric precancerous lesions: observational cohort study in a low risk Western population

Abstract: ObjeCtiveTo accurately measure the incidence of gastric cancer among patients with gastric precancerous lesions, and to quantify the excess incidence in comparison with people with normal mucosa on endoscopy and a general population. DesignPopulation based cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
195
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(210 citation statements)
references
References 30 publications
6
195
1
8
Order By: Relevance
“…Moreover, the prevalence of H. pylori increases with age [6,14,25,43]. Our results also showed a further decrease of PG I at the follow-up in groups with already decreased PG I level at baseline, mostly in age groups > 70 years, thus signaling the continuous progression of mucosal changes.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Moreover, the prevalence of H. pylori increases with age [6,14,25,43]. Our results also showed a further decrease of PG I at the follow-up in groups with already decreased PG I level at baseline, mostly in age groups > 70 years, thus signaling the continuous progression of mucosal changes.…”
Section: Discussionsupporting
confidence: 64%
“…However, the first specific recognizable step in the precancerous process is GA, defined as the loss of normal glandular tissue [3,5]. In addition, GA is the endpoint of chronic processes, such as chronic gastritis associated with Helicobacter pylori (H. pylori) infection, autoimmunity directed against gastric glandular cells and influence of some other environmental factors [3,5,6]. Although in most developed countries H. pylori now infects less than 20% of adults and 5% of children [7], it has been estimated that GA may still develop in 40-50% of H. pylori-infected individuals, while 1-2% of infected individuals will develop GC during their lifetime [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mc Carthy et al [34] have also reported that COX-2 expression in the gastric antrum was reduced by H. pylori eradication therapy. Intestinal metaplasia including dysplasia is widely recognized as a common route to the intestinal type of non-cardia gastric cancer, and Song et al [35] have recently reported that 1 in 39 patients with intestinal metaplasia will develop gastric cancer within 20 years. Kyoto Global Consensus documents provided that the extent of intestinal metaplasia was also associated with the risk of development of gastric cancer in H. pylori gastritis [17].…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce this impact and to improve the outcomes in gastric cancer patients, some necessary steps had been proposed including establishing an improved sanitation system and ensuring access to potable water, which will reduce the infection of Helicobacter pylori of drinking water and ultimately will reduce the incidence of gastric cancer (18). Additional steps to take in Mexico, includes the implementation of a screening system in highrisk population in order to detect early gastric cancer cases, the improvement in the surgical management of gastric cancer cases according with the Japanese guidelines, and the establishment of a multimodality approach to gastric cancer treatment that involves participation of a variety of experts incorporating gastroenterologists, gastric surgeons, oncologists, radiation oncologists and others (19).…”
Section: Management and Outcomesmentioning
confidence: 99%